Investment Analysis and the Adjustment of Stock Prices to Common Information - Brennan, Michael J.; Jegadeesh, Narasimhan; Swaminathan, Bhaskaran (Review of Financial Studies, 1993)
[In this article we are concerned with the effect of the number of investment analysts following a firm on the speed of adjustment of the firm's stock price to new information that has common effects across firms. It is found that returns on portfolios of firms that are followed by many analysts tend to lead those of firms that are followed by fewer analysts, even when the firms are of approximately the same size. Many analyst firms also tend to respond more rapidly to market returns than do few analyst firms, adjusting for firm size. This relation, however, is nonlinear, and the marginal effect of the number of analysts on the speed of price adjustment increases with the number of analysts.]